2014
DOI: 10.1007/s12262-014-1063-0
|View full text |Cite
|
Sign up to set email alerts
|

Negative Appendectomy: an Audit of Resident-Performed Surgery. How Can Its Incidence Be Minimized?

Abstract: Negative appendectomy remains a concern in current surgical practice. Data from the developing world is scarce. Data of appendectomies during the last 5 years were analyzed. Interval and incidental appendectomies were excluded. The demographic details, presenting complaints, clinical signs, and investigations performed were recorded in a predesigned proforma. The data were critically analyzed. Six hundred eighty-five appendectomies were performed during the period. One hundred eighty-five patients with a norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 24 publications
4
28
1
Order By: Relevance
“…Despite all of the developments in diagnosis and treatment methods, high NA and perforation rates have still been reported (13-36%, 12-21%, respectively). [4,10,12,[19][20][21][22] Perforation rates can reach 50%, particularly among the elderly. [3,5,6,22] As perforation rates increase, the rates of morbidity and mortality, the duration of hospital stay, and medical costs increase as well.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all of the developments in diagnosis and treatment methods, high NA and perforation rates have still been reported (13-36%, 12-21%, respectively). [4,10,12,[19][20][21][22] Perforation rates can reach 50%, particularly among the elderly. [3,5,6,22] As perforation rates increase, the rates of morbidity and mortality, the duration of hospital stay, and medical costs increase as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, high NARs were also reported in previous studies conducted in our country and in others worldwide. [3,10,11] Therefore, to analyze the effect of the proposed cut-off values in the present study, the actual and recalculated NARs were compared and the difference was found to be almost significant. We believe the cut-off values proposed in our study, particularly in equivocal cases, may have a value in the diagnosis of AA and thus may help decrease NAR.…”
Section: Discussionmentioning
confidence: 91%
“…High NARs have been reported in our country as well as in some other countries. [3,10,11] Recently, diagnostic values of MPV, RDW, and NLR are increasingly being evaluated in patients with suspected AA, although largely varied results have been reported. [12,13] To our knowledge, there are no published studies that have investigated the role of these inflammatory markers in decreasing NAR based on CT findings of AA.…”
Section: Discussionmentioning
confidence: 99%
“…As in our country, high rates of appendicitis cases have been reported in some other countries (15). Therefore, more effort should be made in order to reduce the incidence of NAR and its complications on patients and hospitals (16). Negative appendectomies lead to both postoperative complications, increased morbidity and mortality rates and costs.…”
Section: Discussionmentioning
confidence: 99%